Emptiness - Yow, Chong Lee (2015)
This series of photographs attempt to capture emptiness around us, focusing particularly on dinning table. For many, dinning table is the shared space where food is savoured with friends and family. In modern living, however, with reasons which encompass longer working hours and isolation due to obsession with IT devices, many have figuratively eat by themselves, alone. These photographs, presented in a rather playful manner, attempt to capture the feeling of emptiness lies beneath us.